Reflection Upon the Practice and Profile of the Movement of the Planes of Thought in Pre-Service Teachers of Science Through the Use of 360° Video Recordings - Joglar-Campos, C (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2019)
This study aimed to identify the profile that pre-service teachers exhibit when they reflect on their practice based on 360 degrees video recordings, and how this methodology has an impact on the movement of this reflection from one plane of development of thought to another. An analysis was made of 11 personal interviews and protocols, answered by pre-service chemistry and biology teachers. The profile identified shows that, even though the teachers are undergoing initial training, the methodology used allows them to transit from a procedural-operative plane, which focuses on content and strategies, to the personal-significative plane, which is concerned with the personal meanings of the teaching done in the classes analyzed. It was also possible to identify that 2 of the subjects studied moved toward a relational-social plane, where their reflection was focused on their students. Unlike other methodologies used to promote the reflection from practice, this methodology allows the pre-service teachers not only to focus their reflection on their performance, but also to be concerned about how the students learn and what emotions are generated in the space generated for the reflection.